Prevalence of obesity in affluent school children of Greater Noida, Uttar Pradesh - Mahato, Mathura Prasad; Chandra, Subhas; Bhattacharjee, Prasun (Indian Journal of Child Health, 2015)
Background: Childhood obesity is a state of over nutrition with long term complications such as hypertension, coronary artery disease and Type-2 diabetes. It also adversely affects psychological development causing poor body image and low self-esteem. Objective: The aim of this study was to know the prevalence of obesity in affluent school children of Greater Noida, Uttar Pradesh. Methods: This study was carried out in affluent school children of four private schools in Greater Noida, Uttar Pradesh. Height and weight of each child weremeasured, and body mass index was determined according to Quetelet’s index. Results: Totally 816 school children of 6-11 years were examined with 528 boys and 288 girls. The overall prevalence of obesity was 7.4% without significant difference in boys (7.3%) and girls (7.6%). Prevalence of obesity was high at the age of 11 years both in boys (12.2%) and girls (11.5%). Conclusion: The present study revealed that obesity has a high prevalence reaching to epidemic proportions in the affluent school children of Greater Noida, Uttar Pradesh.